Resourse-saving technology - N.A.Mamadjonova (Indonesian Journal of Innovation Studies, 2019)
In agriculture, special attention should be paid to reducing the cost of the product using innovative technologies that minimize the cost of fertilizers, fuels, and lubricants, mechanization services for the placement of fertile varieties in conditions of appropriate soil and climate based on the integration of science, education and practice.